Department of Oral Biology Faculty of Dentistry Hasanuddin University Makassar, Indonesia - Asmawati Asmawati (DiscoverSys Inc., 2011)
Oral infections can be caused by the many microorganisms that occupy the oral cavity. Tongue is one of thevulnerable areas of the oral cavity occupied by microorganisms, in which colonized bacteria may cause disease.Mechanical tongue cleansing using tongue scraper can reduce anaerobic bacteria on dorsal of the tongue. Theobjective of this study was to observe the difference of anaerobic bacteria amount on dorsal of the tongue before andafter mechanical tongue cleansing using tongue scraper. This was laboratory experimental study with sampleconsists of 25 students selected by random sampling method. The results showed that the amount of bacteria isdecreased approximately 28% after tongue cleansing using tongue scraper. Based on the statistical analysis with tteston Î±=0.05, there is a difference on the amount of anaerobic bacteria on dorsal of the tongue before and aftermechanical tongue cleansing using tongue scraper.